Functional cross talk between the Fanconi anemia and ATRX/DAXX histone chaperone pathways promotes replication fork recovery - Raghunandan, Maya (Hum Mol Genet, 2020)
Fanconi anemia (FA) is a chromosome instability syndrome characterized by increased cancer predisposition. Specifically, the FA pathway functions to protect genome stability during DNA replication. The central FA pathway protein, FANCD2, locates to stalled replication forks and recruits homologous recombination (HR) factors such as CtBP interacting protein (CtIP) to promote replication fork restart while suppressing new origin firing. Here, we identify alpha-thalassemia retardation syndrome X-linked (ATRX) as a novel physical and functional interaction partner of FANCD2. ATRX is a chromatin remodeler that forms a complex with Death domain-associated protein 6 (DAXX) to deposit the histone variant H3.3 into specific genomic regions. Intriguingly, ATRX was recently implicated in replication fork recovery; however, the underlying mechanism(s) remained incompletely understood. Our findings demonstrate that ATRX forms a constitutive protein complex with FANCD2 and protects FANCD2 from proteasomal degradation. ATRX and FANCD2 localize to stalled replication forks where they cooperate to recruit CtIP and promote MRE11 exonuclease-dependent fork restart while suppressing the firing of new replication origins. Remarkably, replication restart requires the concerted histone H3 chaperone activities of ATRX/DAXX and FANCD2, demonstrating that coordinated histone H3 variant deposition is a crucial event during the reinitiation of replicative DNA synthesis. Lastly, ATRX also cooperates with FANCD2 to promote the HR-dependent repair of directly induced DNA double-stranded breaks. We propose that ATRX is a novel functional partner of FANCD2 to promote histone deposition-dependent HR mechanisms in S-phase.